Navigating the Aesthetics Landscape of Chopin's Largo From Sonata for Cello and Piano Op. 65: A Literary Approach Towards Chamber Music - Swara, Lintang Pramudia (Sekolah Tinggi Teologi Abdiel, 2024)
The realm of musical aesthetics offers an endless source of exploration and interpretation. Within the Romantic era, Frédéric Chopin stands as a towering figure, renowned for his piano masterpieces. Yet, his genius extended beyond the piano, as he also crafted exquisite works for cello and piano. This article delves into the aesthetic landscape of Chopin's Cello Sonata, Op. 65, specifically focusing on the Largo movement. Employing a qualitative approach, the study examines the musical score, engages in historical and literary analysis, and observes live performances. This multifaceted approach reveals an expansion in Chopin's compositional techniques and unveils a rich aesthetic dimension that transcends the simplistic dichotomy of intramusical and extramusical elements. To fully grasp the profound impact of Chopin's Largo movement, the study incorporates a music literature approach. This approach illuminates the transformative power of chamber music, extending its influence beyond the realms of philosophical knowledge and performance aspects into a deeper, more transcendent dimension.